2017
DOI: 10.1111/pce.12951
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolic analyses provide new insights into chilling injury in peach fruit

Abstract: Low temperature conditioning (LTC) alleviates peach fruit chilling injury but the underlying molecular basis is poorly understood. Here, changes in transcriptome, ethylene production, flesh softening, internal browning and membrane lipids were compared in fruit maintained in constant 0 °C and LTC (pre-storage at 8 °C for 5 d before storage at 0 °C). Low temperature conditioning resulted in a higher rate of ethylene production and a more rapid flesh softening as a result of higher expression of ethylene biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 107 publications
7
85
1
1
Order By: Relevance
“…EIL3 induction under cold storage in SE late varieties was also shown in the chilling sensitive variety Hujingmilu (Wang et al ). EIL3 is located on a ‘harvest date’ QTL (Wang et al ), becoming a good candidate to link harvesting time with susceptibility to chilling injury. EIN3/EIL1 target secondary response factors (ERFs) which, in turn, regulate genes underlying ripening‐related traits.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…EIL3 induction under cold storage in SE late varieties was also shown in the chilling sensitive variety Hujingmilu (Wang et al ). EIL3 is located on a ‘harvest date’ QTL (Wang et al ), becoming a good candidate to link harvesting time with susceptibility to chilling injury. EIN3/EIL1 target secondary response factors (ERFs) which, in turn, regulate genes underlying ripening‐related traits.…”
Section: Discussionmentioning
confidence: 76%
“…Ethylene biosynthesis, transduction and signaling are affected by cold storage (Fig. A, B; Tanou et al , Wang et al ). Most of the genes involved in these processes displayed a variety‐specific expression pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peach can develop chilling injury (CI) during cold storage or after transfer to the shelf when the fruit were stored for long periods [1,2]. The most common symptoms of CI in peach are internal browning (IB) of flesh and impairment of softening [3].…”
Section: Introductionmentioning
confidence: 99%
“…This process of exposing fruit to moderate temperatures before cold storage is also termed 'cold acclimation' or 'conditioning' (Hatton, 1990;Wang, 1993). It was recently shown that LTC treatments prior to cold storage alleviated peel browning in 'Huangguan' and 'Nanguo' pears and reduced CI symptoms in stored mango fruit (Li et al, 2017a;Wang et al, 2017b;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%